Diversity of Selaginella across altitudinal gradient of the tropical region - AHMAD DWI SETYAWAN; JATNA SUPRIATNA; DEDY DARNAEDI; ROKHMATULOH ROKHMATULOH; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO (Biodiversitas Journal of Biological Diversity, 2016)
Setyawan AD, Supriatna J, Darnaedi D, Rokhmatuloh, Sutarno, Sugiyarto. 2016. Diversity of Selaginella across altitudinal gradient of the tropical region. Biodiversitas 17: 384-400. Selaginella prefers moist environment for its growth and requires water for fertilization; therefore it is often found flourish in plateau and hilly mountains with high rainfall. The aim of this research was to know species diversity of Selaginella along altitudinal gradient in the southern part of Java, Indonesia. The research was conducted between July 2007 and January 2014across the altitudinal region of Java, Indonesia, which includes the districts of Wonosobo, Purworejo, Kebumen, Banjarnegara and its border areas, with altitudes between 0 and 2500 m. asl. The research found 12 selaginellas species, 10 species collected from field research, namely: S. aristata, S. ciliaris, S. intermedia, S. involvens, S. opaca, S. ornata, S. plana, S. repanda, S. remotifolia, and S. uncinata; and two species only known from herbarium collection of Herbarium Bogoriense (BO), namely S. singalanensis and S. willdenowii. This research was the first publication of the Selaginella flora along altitudinal gradient from the coastal area to the high mountains of Central Java, Indonesia.